Salicylic acid regulates basal resistance to fusarium head blight in wheat - Makandar, Ragiba; Nalam, Vamsi J.; Lee, Hyeonju; Trick, Harold N.; Dong, Yanhong; Shah, Jyoti (My University, 2012)
Fusarium head blight (FHB) is a destructive disease of cereal crops such as wheat and barley. Previously, expression in wheat of the Arabidopsis NPR1 gene (AtNPR1), which encodes a key regulator of salicylic acid (SA) signaling, was shown to reduce severity of FHB caused by Fusarium graminearum. It was hypothesized that SA signaling contributes to wheat defense against F. graminearum. Here, we show that increased accumulation of SA in fungus-infected spikes correlated with elevated expression of the SA-inducible pathogenesis-related 1 (PR1) gene and FHB resistance. In addition, FHB severity and mycotoxin accumulation were curtailed in wheat plants treated with SA and in AtNPR1 wheat, which is hyper-responsive to SA. In support of a critical role for SA in basal resistance to FHB, disease severity was higher in wheat expressing the NahG-encoded salicylate hydroxylase, which metabolizes SA. The FHB-promoting effect of NahG was overcome by application of benzo (1,2,3), thiadiazole-7 carbothioic acid S-methyl ester, a synthetic functional analog of SA, thus confirming an important role for SA signaling in basal resistance to FHB. We further demonstrate that jasmonate signaling has a dichotomous role in wheat interaction with F. graminearum, constraining activation of SA signaling during early stages of infection and promoting resistance during the later stages of infection.
Citation: Makandar, R., . . . & Shah, J. (2012). Salicylic Acid Regulates Basal Resistance to Fusarium Head Blight in Wheat. Molecular Plant-Microbe Interactions, 25(3), 431-439. https://doi.org/10.1094/MPMI-09-11-0232
Keywords: Fusarium head blight; Wheat; Salicylic acid; Fusarium graminearum